Analysis of Biomechanical Characteristics of Volleyball Players' Ankle Joint Movement in Compound Sports Mode Based on Computer Simulation. Issue 3 (October 2020) - Hu, Rongxun
Abstract: The truth of winning a volleyball match at the level of pupil is always to jump higher, attack stronger and move faster. The basis of jump height, the rapid formation of offensive tactics and the fundamental of moving speed have an important impact on the performance of volleyball players. Combining with the characteristics of volleyball events, this paper uses computer simulation technology, chooses representative compound movements: running stop and then forward start, running stop and then lateral start, and running stop and then turning 180 degrees to start. The biomechanical study of ankle joint movement characteristics is carried out. To provide a theoretical basis for a comprehensive understanding of the related muscular participation mechanism of tennis players' ankle joint movement, and to reduce the incidence of ankle joint injury in sports, put forward methods to prevent and avoid injury, so as to provide a reference for the methods and means of daily training and competition of ankle joint.